Body Composition in Elite Strongman Competitors. Issue 12 (December 2020) - Kraemer, William J.; Caldwell, Lydia K.; Post, Emily M.; DuPont, William H.; Martini, Emily R.; Ratamess, Nicholas A.; Szivak, Tunde K.; Shurley, Jason P.; Beeler, Matthew K.; Volek, Jeff S.; Maresh, Carl M.; Todd, Janice S.; et al.
Abstract : Abstract: Kraemer, WJ, Caldwell, LK, Post, EM, DuPont, WH, Martini, ER, Ratamess, NA, Szivak, TK, Shurley, JP, Beeler, MK, Volek, JS, Maresh, CM, Todd, JS, Walrod, BJ, Hyde, PN, Fairman, C, and Best, TM. Body composition in elite strongman competitors. J Strength Cond Res 34(12): 3326–3330, 2020—The purpose of this descriptive investigation was to characterize a group of elite strongman competitors to document the body composition of this unique population of strength athletes. Data were collected from eligible competitors as part of a health screening program conducted over 5 consecutive years. Imaging was acquired using dual-energy x-ray absorptiometry (DXA), providing total body measures of fat mass, lean mass, and bone mineral content (BMC). Year to year, testing groups showed a homogenous grouping of anthropometric, body composition, and bone density metrics. Composite averages were calculated to provide an anthropometric profile of the elite strongman competitor ( N = 18; mean ± SD ): age, 33.0 ± 5.2 years; body height, 187.4 ± 7.1 cm; body mass, 152.9 ± 19.3 kg; body mass index, 43.5 ± 4.8 kg·m −2 ; fat mass, 30.9 ± 11.1 kg; lean mass, 118.0 ± 11.7 kg, body fat, 18.7 ± 6.2%, total BMC, 5.23 ± 0.41 kg, and bone mineral density, 1.78 ± 0.14 g·cm −2 . These data demonstrate that elite strongman competitors are among the largest human male athletes, and in some cases, they are at the extreme limits reported for body size and structure. Elite strongman competitors undergo a high degree of mechanical stress, providing further insight into the potent role of physical training in mediating structural remodeling even into adulthood. Such data provide a glimpse into a unique group of competitive athletes pushing the limits not only of human performance but also of human physiology.